Respuesta :

For the given geometric sequence, we have:

[tex]a_1 = 9\\\\a_n = (-1/3)*a_{n-1}[/tex]

So the correct option is B.

Which is the recursive formula?

Here we have the geometric sequence:

[tex]a_n = 9*(-\frac{1}{3} )^{(n - 1)}[/tex]

To get the initial value of the geometric sequence, we just need to replace n by 1, so we get:

[tex]a_1 = 9*(-\frac{1}{3} )*(1 - 1) = 9[/tex]

Now, notice that the common ratio is (-1/3), this means that each term of the sequence is (-1/3) times the previous term.

[tex]a_n = (-1/3)*a_{n-1}[/tex]

Then the correct option is B.

If you want to learn more about geometric sequences:

https://brainly.com/question/1509142

#SPJ1